2007
DOI: 10.1182/blood-2006-11-055764
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal activation and cytokine spectra in lymph nodes of people chronically infected with HIV-1

Abstract: There is growing recognition that HIV-1 infection leads to an activation of the immune system that includes perturbations of cytokine expression, redistribution of lymphocyte subpopulations, cell dysfunction, and cell death. Here, we explored the relationships between HIV-1 infection and immune activation in chronically HIV-1-infected human lymph nodes. In addition to CD4 T-cell depletion, we found increased effector T-cell frequencies associated with profound up-regulation of an activation marker

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(169 citation statements)
references
References 54 publications
5
162
1
1
Order By: Relevance
“…We observed that CD8 + T cells are more susceptible to cytokine stimulation, since CD8 + T cells, in contrast to CD4 + T cells, were strongly activated (assessed by coexpression of CD38 and HLA-DR and proliferation) by cytokines present during untreated HIV-1 infection, such as IL-15 and IL-12 (11). A different susceptibility toward cytokine activation was also apparent between different T cell subsets, with memory CD8 + T cells being activated more efficiently than naive CD8 + T cells by in vitro cytokine stimulation.…”
Section: Ontinuous Loss Of Cd4 + T Cells and Hyperactivation Of T Cmentioning
confidence: 82%
See 1 more Smart Citation
“…We observed that CD8 + T cells are more susceptible to cytokine stimulation, since CD8 + T cells, in contrast to CD4 + T cells, were strongly activated (assessed by coexpression of CD38 and HLA-DR and proliferation) by cytokines present during untreated HIV-1 infection, such as IL-15 and IL-12 (11). A different susceptibility toward cytokine activation was also apparent between different T cell subsets, with memory CD8 + T cells being activated more efficiently than naive CD8 + T cells by in vitro cytokine stimulation.…”
Section: Ontinuous Loss Of Cd4 + T Cells and Hyperactivation Of T Cmentioning
confidence: 82%
“…Although such cross-reactivity might contribute, it would not readily explain the observation that adenovirus-specific CD8 + T cell responses are similarly affected and that overall levels of CD8 + T cell activation and proliferation correlate with HIV-1 viral load (42,43 T cells much faster than that of CD4 + T cells. So far the relevance of TCR-independent T cell activation, involving cytokine stimulation or engagement of pattern recognition receptors, in chronic HIV-1 infection is not known, but it is possible that the inflammatory environment present during untreated HIV-1 infection has a significant effect on the induction of T cell hyperactivation and consequently contributes to disease progression (8,11,27 + T cells and not CD4 + T cells, both with respect to upregulation of the activation markers CD38 and HLA-DR, which are commonly used to characterize activated T cells in HIV-1-infected patients and with respect to proliferation. Notably, IL-15 activated memory CD8 + T cells more efficiently than naive CD8 + T cells, which is consistent with the notion that activated and memory CD8 + T cells show increased turnover rates in HIV-1-infected patients compared with naive CD8 + T cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility that different cell types account for the observed differences in transporter expression cannot be completely excluded. Evidence exists that HIV infection leads to a hyperplasia of the lymphoid tissue and a perturbation of cytokine expression, redistribution, and sequestration of lymphocyte subpopulations in the LNs (Orenstein et al, 1999;Biancotto et al, 2007). Nevertheless, the higher mRNA levels of the OCTs in the LNs of HIV-infected persons indicate a strongly increased potential for the accumulation of OCT substrates in the LNs.…”
Section: Discussionmentioning
confidence: 95%
“…Significant depletion and functional impairment of both NK and DC compartments have been documented in HIV infection (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) but the mechanisms underlying innate immune dysfunction remain to be elucidated. A loss in circulating CD123…”
Section: H Uman Immunodeficiency Virus Infection Is Associatedmentioning
confidence: 99%